Prevalence and predisposing factors for fatigue in patients with chronic renal disease undergoing hemodialysis: a cross-sectional study - Burdelis, Ricardo Eugenio Mariani; Cruz, Felipe José Silva Melo (São Paulo Medical Journal, 2023)
BACKGROUND: Patients with chronic renal disease and undergoing hemodialysis are at a high risk for developing several complications. Fatigue is a common, troubling symptom that affects such patients and can contribute to unfavorable outcomes and high mortality. OBJECTIVE: This cross-sectional study aimed to evaluate the prevalence of fatigue in Brazilian patients with chronic kidney disease undergoing hemodialysis and determine the predisposing factors for fatigue. DESIGN AND SETTING: An observational, cross-sectional, descriptive study was conducted in two renal replacement therapy centers in the Greater ABC region of São Paulo. METHODS: This study included 95 patients undergoing dialysis who were consecutively treated at two Brazilian renal replacement therapy centers between September 2019 and February 2020. The Chalder questionnaire was used to evaluate fatigue. Clinical, sociodemographic, and laboratory data of the patients were recorded, and the Short Form 36 Health Survey, Pittsburgh Sleep Quality Index, and Beck Depression Inventory were administered. RESULTS: The prevalence of fatigue in patients undergoing hemodialysis was 51.6%. Fatigue was independently associated with lower quality of life in terms of physical and general health. Patients with fatigue had a higher incidence of depression (65.9% vs. 34.1%, P = 0.001) and worse sleep quality (59.1% vs. 49.9%; P = 0.027) than those without fatigue. CONCLUSION: Prevalence of fatigue is high in patients undergoing hemodialysis and is directly related to physical and general health.